PtAu catalyst with enhanced activity for formic acid oxidation - Jelena R. Rogan; Vladislava M. Jovanović; Wohlmuther Aleksandra Gavrilović; Velimir R. Radmilović (Zaštita Materijala)
PtAu systems are recognized as good catalysts for the oxidation of formic acid electrooxidation, which is investigated as a possible anodic reaction in low-temperature fuel cells. In this research, bimetallic PtAu nanoparticles, supported on high area carbon Vulcan XC-72R, were synthesized by water in oil microemulsion method. The precursor reduction process took place in a single microemulsion, simultaneously, in the presence of 35% of HCl in the water phase, as a capping agent. Electrochemical behavior of the PtAu/C catalyst was investigated at as prepared electrodes by cyclic voltammetry in 0.5M H2SO4 as a supporting electrolyte, and also in the oxidation of adsorbed CO. The results were compared to the Pt/C catalyst prepared by the same synthesis procedure. PtAu/C catalyst powder was also characterized by X-Ray Diffraction (XRD), High Resolution Transmission Electron Microscopy (HRTEM) and Energy Dispersive X-Ray Spectroscopy (EDS). Average particle diameter, of 2nm, was calculated from XRD data, which is close to the value of 2.82 nm obtained from TEM images. Compared to identically synthesized Pt nanoparticles, the bimetallic ones are significantly smaller. EDS maps of PtAu/C sample confirm the presence of both elements, and indicate a very fine distribution of Au in the sample. Elemental composition of about 20% Au and 80% Pt was also determined from these maps. Prepared catalyst was tested for formic acid electro-oxidation in terms of its activity and stability over the long term cycling. The voltammograms recorded indicate the change of reaction mechanism and better utilization of the catalyst surface in comparison to Pt/C.